Mūsdienu folklora elektroniskajos plašsaziņas līdzekļos. - Ļevčuka, Anna (Latvijas Universitāte, 2012)
Anna Ļevčuka Mūsdienu folklora elektroniskajos plašsaziņas līdzekļos: bakalaura darbs – Rīga, 2012. – 43.lpp. Šīs darbs ir veltīts mūsdienu folkloras (kura atrodama elektroniskajos plašsaziņas līdzekļos) pētījumam. Pētījuma mērķis ir elektronisko plašsaziņu līdzekļu folkloru tēmu, žanru un specifisko īpašumu pētījums. Pirmajā teoretiskajā daļā atrodami: jautājuma vēsture un folkloru žanru būtība. Otrajā praktiskajā daļā atrodama folkloru vienību analīze. Šīs pētījums var būt interesants gan filoloģiem, gan psiholoģiem kuri interesējas par cilvēku reakciju dažadām ziņām, atrodamām masu medijās.

Anna Levcuka Contemporary folklore in the electronic news media: bachelor work – Riga, 2012 – 43 p. The work is devoted to the study of folklore in the modern news media. The aim of this study is to examine the topics, genres, and the distinguishing features of folklore presented in the electronic media. The first, theoretical part presents: the background of the topic, description and history of the genres of folklore, which can found in the electronic news media. The second, practical part, presents the analysis of folk pieces, found in the electronic news media. This study may be the matter of interest both for linguists and writers, students, studying literary and linguistic process in modern folklore, as well as sociologists, psychologists who study the nature of human reaction to certain events that are broadcasted by the media.
Contemporary Folklore in the Electronic News Media.
Keywords: Valodniecība